Extravasation of 3% NaCl (Sodium Chloride) in Patients with Electrolyte Imbalance: A Case Report - Vini Febriyani Zulfa; Christine E Coyle (PT.Mantaya Idea Batara, 2025)
Abstract: Extravasation resulting from the administration of hypertonic electrolyte solutions, such as 3% sodium chloride (NaCl 3%, 513 mEq/L sodium, 1027 mOsm/L), a hyperosmolar agent, can pose a significant risk of local tissue injury, particularly when administered via peripheral vein access. Peripheral vein access is commonly used for IV therapy, including the administration of medications, blood products, and fluids, but it carries an elevated risk of extravasation. Methods: A literature review was conducted to evaluate clinical approaches for managing extravasation, including the application of hydrocolloid dressings, warm compresses, and saline irrigation. Results: A 61-year-old female presented to the emergency department with complaints of pain, erythema, and swelling in the left arm, which had progressively worsened over the previous two days. The symptoms were localized to the site of a previous peripheral IV insertion, where 3% sodium chloride had been administered during prior inpatient treatment. Conclusion: Extravasation of hypertonic electrolyte solutions such as 3% NaCl can lead to serious local tissue damage if not managed promptly. Close monitoring of infusion sites is essential to prevent complications.